Error Performance Analysis in Underwater Acoustic Noise With Non-Gaussian Distribution - Nor Shahida Mohd Shah; Yasin Yousif Al-Aboosi; Musatafa Sami Ahmed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
There is a high demand for underwater communication systems due to the increase in current social underwater activities. The assumption of Gaussian noise allows the use of Traditional communication systems. However, the non-Gaussian nature of underwater acoustic noise (UWAN) results in the poor performance of such systems. This study presents an experimental model for the noise of the acoustic underwater channel in tropical shallow water at Desaru beach on the eastern shore of Johor in Malaysia, on the South China Sea with the use of broadband hydrophones. A probability density function of the noise amplitude distribution is proposed and its parameters defined. Furthermore, an expression of the probability of symbol error for binary signalling is presented for the channel in order to verify the noise effect on the performance of underwater acoustic communication binary signalling systems.